How does job insecurity relate to adaptive performance? - Niessen, Cornelia; Mäder, Inge (17th congress of the European Association of Work and Organizational Psychology, 2015)
Niessen, C. & Mäder, I. (2015, May). How does job insecurity relate to adaptive performance?. Paper presented at the 17th congress of the European Association of Work and Organizational Psychology, Oslo, Norway.